Feasibility study of compressed bricks utilizing rubber glove manufacturing residue - Soo S.-Q.; Ean L.-W.; Ng C.-Y.; Tan J.-C. (EDP Sciences, 2023)
The demand of the rubber glove had increased significantly since early of the year 2020 due to the COVID-19 virus breakout especially in the medical and healthcare sector. Rubber Glove Manufacturing Residue (RGMR) is the by-product from the effluent treatment by coagulation process in the manufacturing procedure. Non-recyclable RGMR are disposed to landfill after treated. This research is aimed to reuse the RGMR in cemented interlocking bricks to address the natural resources depletion issues and greenhouse gases released from the burnt brick production. The comparison in terms of physical and mechanical properties was conducted in between RGMR and crumb rubber interlocking bricks (RIB). RGMR and crumb rubber were used as partial fine aggregate replacement by 10% while fly ash was used as a cement replacement material by 56%. Four mixes were tested, and the interlocking bricks were categorized as medium weight bricks. However, only control mix and RGMR-2 mix fulfilled the loadbearing masonry requirement of a minimum of 13.8 MPa. RGMR-2 utilizing 10% fine aggregate replacement using RGMR without cement replacement. As for the mixes utilizing fly ash and fine aggregate replacement, RGMR-1 mix and RIB mix show compressive strength of 12.15 MPa and 11.64 MPa respectively. Besides that, the use of RGMR reduced the water absorption compared to RIB mix due to the larger particle size of crumb rubber. The water absorption rate for RIB mix has exceeded the limit of water absorption for the medium weight bricks of 240 kg/m3. The finding indicates that the RGMR exhibited a better performance as compared to the crumb rubber. The Authors, published by EDP Sciences.